Penentuan Absorpsi Suara dan Absoprsi Air oleh Papan komposit Berbahan Kardus Telur - Riska Aldania; Suparno (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine the effect of the thickness of composite boards made from egg cardboard on sound absorption and water absorption. Composite boards are produced by crushing egg cartons with a blender, mixing them with water and tapioca glue to form slurry and then molding them to thicknesses varying from 1, 2, and 3 cm. The sound absorption results were measured using a Sound Level Meter GM1352, while the water absorption capacity was determined using the mass ratio before and after immersion. The results show that the sound absorption capacity of a composite board made from egg cardboard with a thickness of 1 cm is 6.58%, a thickness of 2 cm is 10.87%, and a thickness of 3 cm is 16.05%, while the water absorption capacity of a composite board made from egg cardboard with a thickness 1 cm is 29.41%, 2 cm thickness is 31.43%, and 3 cm thickness is 32.91%. This shows that the greater the thickness of the composite board made from egg cartons used, the greater the sound absorbed. Likewise, with the water absorption test, the results showed that the thicker the composite board made from egg cartons used, the greater the water absorption capacity produced.